PERANCANGAN OTOMASI BORANG AKREDITASI DENGAN MENGGUNAKAN MICROSOFT VISUAL BASIC.NET 2008 - YUNIZAL, EDRI (Sainstek : Jurnal Sains dan Teknologi, 2010)
The aim of this study is software design that how to fill accreditation form. The research method is create a model structure with microsoft visual basic.net 2008 in software design. The fist one of model structure in software design is system analysis, holystic design, spesific design and implementation system. The research was found software design can be use for helping how to fill accreditation form at stain batusangkar and redundant can be complete by saving in center of database Key words: automation, accreditation form,  microsoft visual basic.net 2008